The Effect of a Laboratory-Based CTL Model on Social Interaction Among Undergraduate Students in the JPP Program at the Faculty of Engineering, University of Makassar, in the Fantasy Makeup Course - Andi Nur Maida; Izmi Burhanuddin; Rika Riwayani; Ayu Saputri (Universitas Negeri Makassar, 2026)
This study is a quantitative research designed to determine 1. the impact of the Collaborative Teamwork Learning (CTL) model on students’ social interactions in the Fantasy Makeup course and 2. the effect of the practicum-based Collaborative Teamwork Learning (CTL) model on students social interactions in the Fantasy Makeup course within the Bachelor of Home Economics (S1 PKK) program at the Faculty of Home Economics (JPP FT), University of Makassar (UNM). This quantitative research employs a descriptive and inferential approach. The study sample consisted of 29 students, with data collection techniques including observation, documentation, and questionnaires. Data analysis was conducted using descriptive analysis to examine the implementation of CTL and social interaction, as well as simple linear regression analysis to test its influence. Research Results 1. The results indicate that the implementation of CTL based on practical training regarding student social interaction falls into the fair to good category, with indicators of communication and active participation reaching 80%, cooperation 75%, learning readiness 70%, and discipline 60%, which should be improved. 2. The effect of the laboratory-based Collaborative Teamwork Learning (CTL) model on students’ social interaction in the Fantasy Makeup course in the Bachelor of Fine Arts (BFA) program at the Faculty of Fine Arts, University of Makassar (UNM), is positive and significant, with the regression equation Y = 13.20 + 0.72X, a correlation coefficient (r) of 0.72 (strong category), a coefficient of determination of 51.8%, and a significance value of 0.000 < 0.05. This indicates that the CTL model is effective in enhancing communication, cooperation, and active student participation, although it is not yet optimally consistent due to the influence of other factors. In conclusion, it is necessary to motivate students and design more structured and varied laboratory activities to ensure all students are actively engaged, enhance teamwork development through clear role assignments for students, and strengthen regular guidance and feedback to help students become more prepared and disciplined in their studies. This will foster a conducive learning environment that encourages more intensive communication and provides practical facilities to maximize students learning motivation.